SUBSTANTIATION OF THE FASHION SYSTEM AS THE CONCEPT OF FASHION CONDUCT IN MODERN CONSUMER SOCIETY - Chuprina, N. V.; Kolosnichenko, M. V. (Art and Design, 2018)
Determination of the basic principles of formation and distribution of fashion innovations in society in the context of the functioning of the modern fashion system. Characteristics of fashion innovations as objects of the fashion system and means of fashion communication in the modern consumer society. The methods of systematization and actualization of literary-analytical information about the principles and stages of design-activity in the formation and distribution of fashion innovations are used in the paper. Accumulation, systematization and implementation of project information is carried out by studying of specialized professional literature on the design activities of leading design brands. The basic functional categories of the concept of formation and the occurrence of fashion trends in the fashion system are defined and characterized. The description of the main sources of fashion innovations is given, a comparative analysis of the activity of legislators and distributors of fashion objects is conducted, in the context of their role in the formation, introduction and consumption of fashion trends. The principles of mutual influence of the direction of spreading and the speed of the dissemination of fashion innovation in the society of mass consumption are characterized. In the paper, the main factors of the formation of fashion innovations in the system of fashion are formulated and the main functional categories of the fashion system as the integrated concept of fashion conduct in the modern society of consumption are defined. The paper describes the factors of the formation and realization of topical fashion products that are in line with fashion trends. The appropriateness of their adaptation and implementation in the design of fashion clothes of various classes, from prêt-a-porte to mass market as fashion products of the fashion system is substantiated.